Case Report: An Adult Patient With Deficiency of Adenosine Deaminase 2 Resembled Unilateral Frosted Branch Angiitis - Xu, Yufeng; Shan, Yi; Hu, Yin; Cao, Jing; Wang, Yijie; Lou, Lixia; Ye, Panpan (Frontiers in Medicine, 2021)
Purpose: Deficiency of adenosine deaminase 2 (DADA2) is a rare autosomal recessive systemic autoinflammatory disorder. We describe a rare case of an adult patient with DADA2 who presented with unilateral frosted branch angiitis (FBA) combined with branch retinal vein occlusion. Method: Clinical case report. Results: A 31-year-old male patient complained of blurred vision in his right eye for 2 days. His fundus examination showed FBA combined with branch retinal vein occlusion. He had a medical history of intermittent and recurrent fever, skin rash and aphthous ulcer for five years and lacunar infarction for one month. Laboratory examinations showed hypogammaglobulinemia and mild prolonged APTT. Magnetic resonance imaging (MRI) revealed fresh lacunar infarction. The perivascular sheathing of FBA and macular edema was resolved after steroid administration and treatment of intravitreal anti-VEGF injection. During the period of follow-up, the patient subsequently suffered from recurrence of strokes, abnormality of coagulation function, sudden hearing loss of left ear, and diplopia. His gene sequencing results demonstrated several deletion mutations in CECR1 and the diagnosis of DADA2 was eventually confirmed. Conclusions: FBA is one form of vasculitis and can be a very rare ocular manifestation of DADA2.